PEMBENTUKAN KARAKTER ANAK MELALUI LEMBAGA PENDIDIKAN INFORMAL - Kaimuddin Kaimuddin (LPPM IAIN Parepare, 2018)
The focus which studied about educational institution in establishment the character; scope of informal education connection with the character establishment; contribution of family educational institution in establishment of children character. Searching process shows that education institution of formal-informal-nonformal have an important responsibility and strategic in establishment of children character; and informal educational institution has the main responsibility and first one in establishment of children character. The contribution of informal educational institution is very significant in establishment of children character, in family education preceded by the process of children education, love and affection touching, make the children accustomed, and provide an axample become founder formed of children character up to the children grow become adult with intact personality.